Alternative accelerated and short-term methods for evaluating slow crack growth in polyethylene resins with high crack resistance. (September 2017) - Robledo, Nuria; Domínguez, Carlos; García-Muñoz, Rafael A.
Abstract: The current market has widely adopted the new polyethylene pipe grade PE 100 RC (resistant to cracks) for pipe applications. However, the main drawback of this material is the long test period (∼10, 000 h) required for ranking the resins. This paper proposes a modified Pennsylvania edge-notch tensile (PENT) test with higher load and temperature conditions (2.8 MPa and 90 °C). With the modified PENT test, failure time is six times shorter but slow crack growth is maintained. Additionally, it evaluates and finds an unexpected relationship between the strain hardening modulus and specimen thickness. These results suggest that the 0.30-mm thickness recommended by ISO 18488 is not optimal. Therefore, thicker specimens are proposed for accurate strain hardening modulus determination. Both methods are viable alternatives for evaluating the failure resistance of the new polyethylene pipe grades.